STRATEGI INOVATIF KEPALA SEKOLAH DALAM PEMENUHAN HONORARIUM GURU TERDAFTAR DAPODIK DI SEKOLAH SWASTA - Fadli Hasan; Dian Hidayati (Manajemen Pendidikan, 2023)
Honorarium for Quality Improvement (HPM) of Educators and Non-State Civil Apparatus (ASN) Education Personnel to improve welfare, quality of performance, and competency development to achieve the goal of education in Bandung. However, HPM for non-ASN honorary teachers has not been fully accommodated for honorary teachers in Bandung. This study aims to describe the system in making honorary teacher honorarium policies in private schools. The approach taken is qualitative, the data comes from observation, interviews, and documents. The research subjects were three private school principals in Bandung, and three school operators there. The first one represents a financially stable school and can make policies without fully involving the foundation. The second, represents a school that is financially secure and the foundation is fully involved in determining school policy. The last, represents a school that is not yet financially secure. The research finding is an alternative policy for the school principal in adapting mayor's regulation which has not yet accommodated honorary teachers for quality improvement honors whose data is based on the system. The steps were taken by private school principals to accommodate honorary teachers by adapting the mayor's regulations which were revealed to be the criteria for awarding honorariums for quality improvement.